Optimization of the lightning warning model for distribution network lines based on multiple meteorological factor thresholds - Wan, Ziyang; Fu, Lixiang; Pu, Ziheng; Du, Zhenchuan; Chen, Zhigang; Zhu, Yi; Ma, Xiaoxin (Frontiers in Energy Research, 2023)
Lightning is one of the frequent natural disasters, which seriously affects the safe secure and stable operation of the power system, especially the distribution network lines with weak reliability. In order to improve the power supply reliability of the distribution network, higher requirements are put forward for the accuracy of lightning warning. Therefore, this paper establishes a lightning warning model based on comprehensive multi-meteorological factor thresholds, and analyzes the meteorological factor data such as atmospheric field strength, echo intensity, echo top height, and vertical cumulative liquid water content under thunderstorm weather. The threshold value of each factor warning is obtained and the corresponding threshold weight is calculated by entropy weight method. According to the weight of each threshold, the comprehensive threshold index of lightning warning is obtained, and the lightning warning is based on this index. A total of 105 lightning data from May to June 2022 in Nanchang City were analyzed as samples. The thresholds of atmospheric field strength, echo intensity, echo top height and vertical cumulative liquid water content were 1.2 kV/m, 40 dBZ, 8 km and 5.2 kg• m -2 , respectively. The corresponding weights of each factor were 0.4188, 0.2056, 0.2105 and 0.165, respectively. This model was used to warn a thunderstorm event in July 2022 in Nanchang area. The success rate of model warning was 0.91, the false alarm rate was 0.11, and the critical success index was 0.80. Compared with the single factor threshold lightning warning model, the warning false alarm rate is reduced by 6% and the critical success index is increased by 14% while ensuring the high warning success rate.